An Analysis of Illocutionary Speech Act in NYU's 2022 Commencement Speech - Khusnah, Nurul Azizatul; Assiddiqi, Hasbi; Listiani, Toneng (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Illocutionary speech acts are actions used by speaker not only to convey utterances, but also have other purposes for conveying meaning. Meanwhile, motivational elements are used by speaker to arouse the enthusiasm of their listeners. This study aims to find out and analyse illocutionary speech acts and how the utterances conveyed motivational elements in New York University (NYU)’s 2022 commencement speech. The data used is a transcript of a video entitled New York University (NYU)’s 2022 Commencement Speaker Taylor Swift. In this research, the researcher uses Searle’s theory to classify and analyze sentences and Daniel Goleman’s theory to classify and analyze motivational elements. This study used qualitative method with descriptive results based on the researcher’s analysis. Bowen’s theory is used as technique analysis in categorizing, describing and drawing a conclusion. The results of illocutionary speech act show that there are 37 data of representative, 9 data of directive, 12 data of expressive, 6 data of commissive and no sentences stated as declarative. The results of motivational elements show that there are 4 data of personal drive motivation, 3 data of commitment motivation, 3 data of initiative motivation and 3 data of optimism motivation. It can be concluded that representative was the most commonly found data because speaker told their life stories, also related to personal drive motivation as the most commonly found data to motivate graduates to improve themselves to achieve their goals.